2014
DOI: 10.1111/ene.12593
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome and post polio syndrome: a case−control study

Abstract: Our findings demonstrate a high prevalence of RLS in PPS, and that RLS occurrence may significantly influence the HRQoL and fatigue of PPS patients. A hypothetical link between neuroanatomical and inflammatory mechanisms in RLS and PPS is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…A sleep study may be required to assess for sleep‐related breathing disorders/sleep apnea. Restless leg syndrome is common in postpolio individuals, with a reported prevalence of 36% among postpolio patients at an outpatient neuromuscular clinic, and may also impact sleep and energy level . Creatine kinase level may be moderately elevated in individuals with poliomyelitis but is not specific for PPS and cannot reliably distinguish between patients with or without PPS .…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sleep study may be required to assess for sleep‐related breathing disorders/sleep apnea. Restless leg syndrome is common in postpolio individuals, with a reported prevalence of 36% among postpolio patients at an outpatient neuromuscular clinic, and may also impact sleep and energy level . Creatine kinase level may be moderately elevated in individuals with poliomyelitis but is not specific for PPS and cannot reliably distinguish between patients with or without PPS .…”
Section: Investigationsmentioning
confidence: 99%
“…Restless leg syndrome is common in postpolio individuals, with a reported prevalence of 36% among postpolio patients at an outpatient neuromuscular clinic, and may also impact sleep and energy level. [129][130][131] Creatine kinase level may be moderately elevated in individuals with poliomyelitis but is not specific for PPS and cannot reliably distinguish between patients with or without PPS. 132,133 Results of the clinical evaluation will indicate whether other medical conditions such as depression, cardiorespiratory disease, inflammatory conditions (e.g., rheumatoid arthritis), chronic pain disorders/fibromyalgia, or medications or lifestyle factors may be responsible for or exacerbate the fatigue and/or pain, and additional investigations, management, or consultations may be required.…”
Section: Investigationsmentioning
confidence: 99%
“…The fatigue severity scale score was significantly higher in patients with post‐polio syndrome who had RLS. The SF‐36 survey results of these patients showed that the physical role, physical function, and subdomains of body pain were negatively affected . In our study, we found that sleep quality was also negatively affected in patients with poliomyelitis who also had RLS diagnosis.…”
Section: Discussionmentioning
confidence: 48%
“…The neuroanatomical similarities between central‐spinal areas affected by poliomyelitis and areas that play a role in RLS development suggest that these patients have a higher risk for RLS development. According to the literature, there are only a limited number of studies or case reports on the association between RLS and poliomyelitis. The aim of this study was to assess the presence of RLS in patients with poliomyelitis, and associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although each is non-specific, it has been proposed that, when used in combination and together with imaging, the specificity for detecting early PD may be increased significantly. Dystonia and other movement disorders are now attracting increasing attention in terms of treatment, particularly with non-medical forms including deep brain stimulation [118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133].…”
mentioning
confidence: 99%